2016
DOI: 10.3329/bjar.v41i1.27673
|View full text |Cite
|
Sign up to set email alerts
|

Responses of garlic to zinc, copper, boron and molybdenum Application in grey terrace soil of amnura soil series

Abstract: A field experiment was conducted at the Spices Research Centre, Shibgonj, Bogra, Bangladesh during rabi (winter) seasons of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
(1 reference statement)
2
3
0
Order By: Relevance
“…The results are in conformity with the findings of Srivastava et al (2005), Rahohida et al (2010, Yousuf et al (2015) and Choudhary et al (2014) in garlic crop. The application of micronutrients soil or foliar spray significantly influenced bulb yield of onion crop (Pramanik and Tripathy, 2017;Singh et al, 2015).…”
Section: Disscussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results are in conformity with the findings of Srivastava et al (2005), Rahohida et al (2010, Yousuf et al (2015) and Choudhary et al (2014) in garlic crop. The application of micronutrients soil or foliar spray significantly influenced bulb yield of onion crop (Pramanik and Tripathy, 2017;Singh et al, 2015).…”
Section: Disscussionsupporting
confidence: 93%
“…Micronutrients takes active part in photosynthesis, which ultimately helps towards increase in number and weight of bulbs. Similarly, significant influence of micronutrients mixture on growth and yield parameters of garlic as reported by Srivastava et al (2005), Rahohidas et al (2010, Yousuf et al (2015), and Choudhary et al (2014) in garlic crop. Pramanik and Tripathy (2017) reported that application of micronutrients mixture have marked influence on growth and yield attributing characters of onion like plant height, number of roots per plant, diameter of bulb and bulb weight as well as bulb height.…”
Section: Disscussionmentioning
confidence: 63%
“…Further, sufficient zinc supply resulted in higher crop growth and zinc uptake. This was in agreement with the findings reported by Yousuf et al (2016) and Alam et al (2019).…”
Section: Zinc Accumulation and Uptakesupporting
confidence: 94%
“…Recently use of micronutrients in improving the crop yields and quality of crop produces are gaining momentum due to the increased awareness on their significance in human health. Among various micronutrients, zinc plays an important role in achieving higher yield and quality of crop produces in many crops (Chitdeshwari et al, 2011;Yousuf et al, 2016). Zinc deficiency in soils and plants is the widest abiotic stress observed worldwide resulting in substantial losses in crop yield and quality crop.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation